HIV-inclusive and -sensitive cash transfer initiatives: Evidence from high-prevalence countries in Eastern and Southern Africa - Pedro Lara de Arruda (International Policy Centre for Inclusive Growth (IPC-IG), 2019)
There is growing consensus that the tools and knowledge exist to end the HIV/AIDS epidemic as a public health threat by 2030. To reach this goal, the Joint United Nations Programme on HIV/AIDS (UNAIDS) has established the 90-90-90 strategy, which aims to ensure that by 2020, 90 per cent of people living with HIV know their HIV status, 90 per cent of people living with HIV receive sustained antiretroviral therapy (ART), and 90 per cent of those receiving ART achieve viral suppression (UNAIDS 2014a). [...]
Keywords: 330; HIV; inclusive; sensitive; cash transfer; initiatives; evidence; high-prevalence; countries; Eastern Africa; Southern Africa